Risk factors for the development of oesophageal adenocarcinoma in Barrett's oesophagus: a UK primary care retrospective nested case–control study. Issue 2 (1st April 2014) - Cooper, SC; Menon, S; Nightingale, PG; Trudgill, NJ
Abstract : Background: Oesophageal adenocarcinoma (OAC) incidence is rising rapidly and prognosis remains poor. Endoscopic surveillance of Barrett's oesophagus (BO) remains controversial. Objective: A nested case–control study was undertaken to evaluate risk factors for progression of BO to OAC, potentially guiding surveillance efforts. Methods: The Health Improvement Network database includes general practitioner consultations from 5 million UK subjects. BO subjects with 1‐year minimum of follow up were followed until development of OAC or end of time on database. Demographic variables (age, gender, smoking, body mass index) and data on medication considered negatively (aspirin/nonsteroidal anti‐inflammatory drugs/proton pump inhibitors) or positively associated (lower oesophageal sphincter‐relaxing and asthma drugs) with OAC development were studied. Cox regression analysis‐derived hazard ratios with 95% confidence intervals estimated the relative risk for OAC progression. Results: A total of 3749 BO subjects were studied: 55 developed OAC during 17, 743 patient years of follow up, a progression rate of 0.3% per annum. There was 96.7% of the cohort who took proton‐pump inhibitors, with no association observed. Increasing age (1.03, 95% CI 1.01–1.05, p = 0.005), male gender (3.06, 95% CI 1.50–6.24, p = 0.002), and having ever smoked (2.36, 95% CI 1.13–4.93, p = 0.023) were associated with progression to OAC, (although smoking lost association on multivariate analysis). Increasing number of drugs used for asthma (2.91, 95% CI 1.10–7.68, p = 0.0314) was also associated. Conclusion: In this nested case–control study of BO, male gender, increasing age, and increasing use of asthma drugs were associated with progression to OAC.